Association of Total Mortality and Cardiovascular Endpoints With the Timing of the First and Second Systolic Peak of the Aortic Pulse Wave - Yi‐Bang Cheng; De‐Wei An; Lucas S. Aparicio; Qi‐Fang Huang; Yu‐Ling Yu; Chang‐Sheng Sheng; Teemu J. Niiranen; Fang‐Fei Wei; José Boggia; Katarzyna Stolarz‐Skrzypek; Natasza Gilis‐Malinowska; Valérie Tikhonoff; et al. (The Journal of Clinical Hypertension)
ABSTRACT Prognostic significance of the timing in the cardiac cycle of the first (TP1) and second (TP2) systolic peak of the central aortic pulse wave is ill‐defined. Incidence rates and standardized multivariable‐adjusted hazard ratios (HRs) of adverse health outcomes associated with TP1 and TP2, estimated by the SphygmoCor software, were assessed in the International Database of Central Arterial Properties for Risk Stratification (IDCARS) (n = 5529). Model refinement was assessed by the integrated discrimination (ID) and net reclassification (NR) improvement. Over 4.1 years (median), 201 participants died and 248 and 159 patients experienced cardiovascular or cardiac endpoints. Mean TP1 and TP2, standardized for cohort, sex, age, and heart rate, were 103 and 228 ms. Shorter TP1 and TP2 were associated with higher mortality and shorter TP1 with a higher risk of cardiovascular and cardiac endpoints (trend p ≤ 0.004). The HRs relating total mortality and cardiovascular endpoints to TP2 were 0.82 (95% confidence interval [CI]: 0.72–0.94) and 0.87 (0.77–0.98), respectively. The HR relating cardiac endpoints to TP1 was 0.81 (0.68–0.97). For total mortality and cardiovascular endpoints in relation to TP2, NRI was significant (p ≤ 0.010), but not for cardiac endpoints in relation to TP1. Integrated discrimination improvement (IDI) was not significant for any endpoint. The HRs relating total mortality to TP2 were smaller (p ≤ 0.026) in women than men (0.67 vs. 0.95) and in older (≥ 60 years) versus younger (< 60 years) participants (0.80 vs. 0.88). Our study adds to the evidence supporting risk stratification based on aortic pulse analysis by showing that TP2 and TP1 carry prognostic information.